INOVASI PEKAN SAGU DAN MOMENT OF TRUTH PELAYANAN PUBLIK DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SELUMA DI ERA VUCA - Rahayu, Desita; Agus, Nour Farozi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2022)
Pekan Sagu innovation is interesting to be observed because the innovation carried out by Disdukcapil at Seluma Regency does not utilize internet facilities, even though the government has determined a digitalization roadmap until 2024. This innovation is carried out door to door. What are the critical moments of public service in Pekan Sagu? This research is a qualitative research with descriptive method. The focus of research on Pekan Sagu moment of service innovation. Moment of Truth relate to the service context and references held by customers and employees. So that innovations that have simplified and perfected services can still lead to administrative pathology, due to face-to-face meetings between the citizen and service providers. Pekan Sagu does not hinder people's workdays and the circle of services is simpler, resulting in perceived value for service recipients. However, the government must still strive for digital-based innovation in order to support the acceleration of digitalization of services.